A New Disruptive Technology for Zero-Brine Discharge: Towards a Paradigm Shift - Estefanía Bonnail; Sebastián Vera; T. Ángel DelValls (Applied Sciences, 2023)
The desalination of aquifers and seawaters is a viable choice to meet primarily domestic and industrial global water requirements. It removes salts from seawater to obtain freshwater with sufficient quality for different purposes, as well as a highly salt-concentrated waste stream known as brine. This residue is usually returned to the ocean, provoking, among other impacts, changes in temperature, salinity and oxygen and overall local aquatic ecosystem stress, as well as social rejection. Desalination in inland aquifers is more complicated because brine disposal is complicated or impossible. The current study presents a new zero-brine discharge technology able to achieve ecological liquid purification through distillation for the separation of the dissolved solids as crystallized salts (Adiabatic Sonic Evaporation and Crystallization, ASE&C). This new technology was used with seawater and three types of brine to test how it would work when coupled with reverse osmosis desalination plants. Analysis of the byproducts after treatment of the seawater and the different brines are presented here. A basic economic approach to calculating potential revenues is also presented. The results of the analyses revealed a complete depuration of water as distilled water, and crystallized solids with highly concentrated commercial salts (with different composition depending on their origin). The estimated economic value of annual revenue (taking into account only seven element recoveries and treatment of a volume of 1000 m3/d) for three types of brines ranged between 1 and 11 million euros, compared to between 3.6 and 9.3 million euros when ASE&C is employed with seawater. The treatment of greater volumes for seawater desalination would increase these numbers significantly. ASE&C supposes a solution coupled (or not) to desalination plants to reduce the ecological impacts associated with brine discharges to zero, obtaining two significant commercial byproducts: (seawater: freshwater and commercial elements Br, Ca, Cs, Cl, NaOH, Mg, N, K, Rb, Na, Sr, Li, U, B, Sr, Ga, etc.; aquifers: a larger list than for saltwater, depending on the nature of the water body). It can solve environmental issues associated with brine discharge, with null CO2 emissions (renewable energy) and profitable (i.e., with no costly pretreatment) technology.